Peran Ganda Wanita Sebagai Ibu Rumah Tangga dan Pendamping Belajar Anak di Masa Pandemi - Berliana berli kurniasari; Nevi Dwi Kirana Nevi Kirana; Aulia Nuroctavia Aulia Nuroctavia; Refti Handini Refti Handini (Pusat Studi Gender dan Anak (PSGA) Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Sultan Maulana Hasanuddin Banten, 2022)
Until now, the Corona-19 Virus Pandemic is still ongoing. It's been about 6 months since the people of Indonesia have complained about the ongoing pandemic. Many problems arise due to this pandemic. The government also issued new policies, including learning which is usually done in schools, campuses, and other agencies must be done online or in the sense that all learning is done at home. This is to reduce the spread of the virus. As a result of this policy, parents of students complain about various obstacles when studying at home. The purpose of this research is to find out the dual role of mothers in taking care of the household and assisting children in learning during the pandemic. This research method is a qualitative research method. It is hoped that this research can solve the problems that are currently happening